Relationship between air pollution and daily psychiatric outpatient visits in Zhengzhou - Deqi KONG; Yan WANG; Huimin HUANG; Ningyi MA; Mengdan QIAN; Ya LI (环境与职业医学, 2023)
BackgroundPsychiatric diseases are a serious threat to human health. Studies have shown an association between ambient air pollution and psychiatric diseases, yet the results are inconsistent. ObjectiveTo explore the potential effects of air pollution exposure on psychiatric diseases using Zhengzhou City as an example. MethodsOutpatient consultation data of the Clinical Psychology Clinic at The First Affiliated Hospital of Henan University of Traditional Chinese Medicine as well as air quality data between 28 October 2013 and 28 August 2019 were collected. The exposure-lag effect between air pollutant exposure and daily outpatient visits was assessed using a distribution lag nonlinear model (DLNM), and subgroup analyses were conducted including sex (male and female), age (<18, 18-59, and >59 years), season (spring, summer, autumn, and winter), and types of diseases (depression and anxiety). ResultsA total of 112986 valid confirmed outpatient visit records for psychiatric diseases were collected. The largest proportions of visits in each subgroup were females, 18-59 years old, spring, and depression. The results of one-day lagged risk of total outpatient visits showed that PM2.5, PM10, SO2, and NO2 all significantly associated with an increased risk of psychiatric outpatient visits. The one-day lagged risk peaks were: PM2.5 (RR=1.0016, 95%CI: 1.0011, 1.0022), PM10 (RR=1.0012, 95%CI: 1.0001, 1.0022), SO2 (RR=1.0060, 95%CI: 1.0002, 1.0117), and NO2 (RR=1.0144, 95%CI: 1.0100, 1.0187). The cumulative lagged risk peaks were: PM2.5 (CumRR=1.0274, 95%CI: 1.0158, 1.0392), PM10 (CumRR=1.0124, 95%CI: 1.0044, 1.0205), SO2 (CumRR=1.0214, 95%CI: 1.0009, 1.0423), and NO2 (CumRR=1.0613, 95%CI: 1.0460, 1.0770). The results of subgroup analysis showed more significant impacts of air pollution exposure on females and people aged 18-59 years, and in winter. To be specific, PM2.5 (RR=1.0022, 95%CI: 1.0006, 1.0037), PM10 (RR=1.0015, 95%CI: 1.0003, 1.0027), SO2 (RR=1.0082, 95%CI: 1.0016, 1.0148), and NO2 (RR=1.0156, 95%CI: 1.0106, 1.0206) exposures associated with an increased risk of outpatient visits for psychiatric disorders in women; PM2.5 (RR=1.0018, 95%CI: 1.0011, 1.0024), PM10 (RR=1.0012, 95%CI: 1.0001, 1.0023), and NO2 (RR=1.0142, 95%CI: 1.0095, 1.0189) associated with an increased risk of visits in those 18-59 years of age; PM2.5 (RR= 1.0043, 95%CI: 1.0001, 1.0085), PM10 (RR= 1.0038, 95%CI: 1.0007, 1.0069), and NO2 (RR= 1.0215, 95%CI: 1.0117, 1.0313) in winter months significantly associated with an increased risk of psychiatric outpatient visits. In addition, the risk of depression and anxiety visits varied depending on the concentration of air pollutants and the duration of exposure. The risk of visits for depression were more affected by CO, NO2, and SO2, and the risk of visits for anxiety were more affected by PM2.5, PM10, and O3. ConclusionExposure to air pollution is associated with an increased risk of psychiatric outpatient visits. The effects vary by air pollutants as well as by sex, age, type of psychiatric illness, and season.